The work to orient the family to the badminton’s (Original) (Revista científica Olimpia, 2021)
The present research deals a current and interesting thematic to the process of the family’ orientation about badminton’ sport. The present diploma-paper has as objective the elaboration of activities to orient the family to the badminton’s category since 9 to10 years old at sportive combined Antonio Maceo Grajales. This research is structured by two chapters, in the first chapter, it is developed the theoretical foundations and it assumes important epismologic criteria, it finishedwith a diagnose that revealed the insufficiencies existed concerning the family' s knowledge to the sport. In the second chapter, it was taken as sample of five trainers and ten families of athletes, to which were applied methods to support and to diagnose the current situation of the problem, it presents the activities of the family’s orientation that it contains the essential elements for the knowledge of the family to the badminton' sport. Finally, the elements presented refer the partial valuation of the activities being revealed the viability and value of its application.
Keywords: orientation; family orientation; educational activities